Monitored Anesthesia Care by Sedation-Trained Providers in Acute Stroke Thrombectomy - Slawski, Diana E.; Salahuddin, Hisham; Saju, Linda; Shawver, Julie; Korsnack, Andrea; Tietjen, Gretchen; Papadimos, Thomas J.; Castonguay, Alicia C.; Kung, Vieh; Burgess, Richard; Zaidi, Syed F.; Jumaa, Mouhammad A. (Frontiers in Neurology, 2019)
Background: Mechanical thrombectomy (MT) for ischemic stroke can be performed under local anesthesia (LA), conscious sedation (CS), or general anesthesia (GA). The need for monitoring by anesthesia providers may be resource intensive. We sought to determine differences in outcomes of MT when sedation is performed by an anesthesia team compared to sedation-trained providers. Methods: We performed a retrospective analysis on patients who were screened by a pre-hospital stroke severity screening tool and underwent MT at two stroke centers. Baseline characteristics, time metrics, sedatives, peri-procedural intubation, complications, and outcomes were recorded. Good outcome was defined as modified Rankin score of ≤2. Results: We analyzed 104 patients (sedation-trained provider = 63, anesthesia team = 41) between July 2015 and December 2017. In the sedation-trained provider group, four patients required intervention by an anesthesia team. There were no differences in patients receiving LA (sedation-trained provider 24% vs. anesthesia team 27% p = 0.82), CS (70 vs. 63%, p = 0.53), or GA (6 vs. 10%, p = 0.71) between groups. Sedation-trained providers were more likely to use only one drug during the procedure (62 vs. 34%, p = 0.009). The rate of procedural complications (9.5 vs. 4.5%, p = 0.48), good outcome (56 vs. 39%, p = 0.11), and mortality (22 vs. 24%, p = 0.82) was similar between groups. Sedation by provider type did not predict functional outcome or mortality at 3 months. Conclusions: Sedation-trained providers are capable of delivering appropriate sedation without compromising patient safety. The use of “as needed” anesthesia teams for MT may have considerable effect on resource allocation and cost.